Discovery of 4-arylquinoline-2-carboxamides, highly potent and selective class of mGluR2 negative allosteric modulators: From HTS to activity in animal models. Issue 9 (1st May 2020) - Shu, Youheng; Diamond, Tracy L.; Hershey, James C.; Huang, Shaei; Magliaro, Brian C.; O'Brien, Julie A.; Schlegel, Kelly-Ann S.; Puri, Vanita; Uebele, Victor N.; Uslaner, Jason M.; Wang, Cheng; Converso, Antonella
Graphical abstract: Abstract: Antagonism of the mGluR2 receptor has the potential to provide therapeutic benefit to cognitive disorders by elevating synaptic glutamate, the primary excitatory neurotransmitter in the brain. Selective antagonism of the mGluR2 receptor, however, has so far been elusive, given the very high homology of this receptor with mGluR3, particularly at the orthosteric binding site. Given that inhibition of mGluR3 has been implicated in undesired effects, we sought to identify selective mGluR2 negative allosteric modulators. Herein we describe the discovery of the highly potent and selective class of mGluR2 negative allosteric modulators, 4-arylquinoline-2-carboxamides, following a successful HTS campaign and medicinal chemistry optimization, showing potent in vivo efficacy in rodent.